2008
DOI: 10.1142/s0219265908002175
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Diagnosability of Cayley Graphs Generated by Transposition Trees Under the Comparison Diagnosis Model

Abstract: The diagnosis of faulty processors plays an important role in multiprocessor systems for reliable computing, and the diagnosability of many well-known networks has been explored. Zheng et al. showed that the diagnosability of *This work was supported in part by the National Science Council of the Republic of China under Contract NSC 95-2221-E-009-134-MY3. 83 J. Inter. Net. 2008.09:83-97. Downloaded from www.worldscientific.com by UNIVERSITY OF QUEENSLAND on 08/16/15. For personal use only. 84 C.-K. Lin et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…Cheng and Lipták [22] further generalized this result to star graphs with linearly many faults. Moreover, in terms of the size of connected components, Hsu et al [14] and Lin et al [13] also showed the conditional diagnosabilities for hypercube and star graphs, respectively. In this paper, based on the fault tolerance of alternating group networks AN n , we establish the conditional diagnosability of alternating group graphs AN n (n 5) under the comparison diagnosis model.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cheng and Lipták [22] further generalized this result to star graphs with linearly many faults. Moreover, in terms of the size of connected components, Hsu et al [14] and Lin et al [13] also showed the conditional diagnosabilities for hypercube and star graphs, respectively. In this paper, based on the fault tolerance of alternating group networks AN n , we establish the conditional diagnosability of alternating group graphs AN n (n 5) under the comparison diagnosis model.…”
Section: Introductionmentioning
confidence: 98%
“…Zheng et al [12] analyzed the diagnosability of star graph under a comparison diagnostic model. Moreover, Lin et al [13] introduced the so-called conditional diagnosis, and showed that the conditional diagnosability of a star graph of size n is 3n − 7, which is about three times larger 0020-0190/$ -see front matter © 2010 Published by Elsevier B.V. doi:10.1016/j.ipl.2010.03.010 that the classical diagnosability of a star graph. In particular, Hsu et al [14] proved that the conditional diagnosability of a hypercube of size n is 3n − 5, based on the idea of Lai et al [15] who was the first to use a restricted diagnosis strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [8] introduced the so-called conditional diagnosability of a system under the situation that no set of faulty vertices can contain all neighbors of any vertex in the system. A faulty set …”
Section: The Conditional Diagnosability Of Cjc Nmentioning
confidence: 99%
“…Sengupta and Dahbura [12] developed this comparison approach such that the comparisons have no central unit involved. Lin et al [8] introduced the conditional diagnosis under the comparison model. By evaluating the size of connected components, they obtained that the conditional diagnosability of Star graph S n is 3n − 7.…”
Section: Introductionmentioning
confidence: 99%
“…Upon the receipt of the two responses, the processor compares them and proclaims that the two neighbors are both fault-free or at least one of them is faulty. Conditional diagnosability for interconnection networks under the MM model has been investigated in various studies [6,11,12,13,14,16,19,25,26].…”
Section: Introductionmentioning
confidence: 99%